ANALISIS PENDAPATAN INDUSTRI MEBEL DI KELURAHAN TUNJUNGSEKAR KECAMATAN LOWOKWARU KOTA MALANG - Natalia Popy Kristian; Idah Zuhroh; Dwi Susilowati (Program Studi Ekonomi Pembangunan, 2019)
This study aims to investigate the characterictics of furniture industry, effect of capital, wages, and long effort towards income of furniture industry in Malang. In this study, researcher uses 30 respondents of stakeholders. The data type used is a cross-section then do hypothesis testing with F-test, t-test, and the coefficient of Determination on error rate α=5%. Furthermore, in this study also analyze cost efficiency and income. The findings of this study shows that capital variable has not significant effect towards income. Whereas, other variable such as wages and long effort have significant impact on the income of furniture industry in Malang. However, simultaneosly capital, wages, and long effort have significant impact. While the value of the coefficient of determination (R2) is 0,48, this indicates the ability of capital variable, wages, and long effort in explaining the amount of income of 48%. In addition, the cost of furniture industry in Malang is quite efficient and has average income 35,7 million.